Determination of chargino and neutralino masses at the International Linear Collider - Li, Y (2011)
A feasibility study is presented which measures the masses of the chargino X̃₁± and neutralinos X̃₁⁰ and X̃₂⁰ using the processes of e⁺e⁻→ X̃₁+X̃₁- → X̃₁⁰X̃₁⁰W⁺W⁻ and e⁺e⁻→ X̃₂⁰X̃₂⁰ → X̃₁⁰X₁⁰ZZ at the International Linear Collider. The detector simulation is based on the Silicon Detector (SiD) concept and an integrated luminosity of 500 fb⁻¹ is considered at the centre-of-mass energy of 500 GeV. A template-fitting method is employed to measure the chargino and neutralino masses, which results in uncertainties of 0.16 GeV, 0.5 GeV and 1.0 GeV for the mass of X̃₁⁰, X̃₁± and X̃₂⁰ respectively. A study on the ISIS2 sensor, a technology for the ILC vertex detector, is also presented. The characteristic of the sensors are studied for both its test structure and main array pixels. The operation conditions are optimized and the sensor successfully demonstrated its capabilities of in-situ charge storage and charge transfer. The charge transfer efficiency is measured to be better than 98%.